Towards a morphological analyzer for the umbundu language - Simões, Alberto (2020)
In this document we present the first developments on an Umbundu dictionary for a jSpell, a morphological analyzer. Initially some comments are performed regarding the Umbundu language morphology, followed by the discussion on jSpell dictionaries structure and its environment. Last, we describe the Umbundu dictionary bootstrap process and perform some final experiments on its coverage.